PENGARUH VARIASI UKURAN BUTIR PASIR CETAK TERHADAP KEKUATAN IMPACT DAN MORFOLOGI PATAHAN HASIL CORAN KUNINGAN PADA PENGECORAN EVAPORATIVE - Pasek Eka Putra, Putu Nanta; Sugita, I Ketut Gede; Kencanawati, Cok Istri Putri Kusuma (Teknik Desain Mekanika, 2023)
Abstractt Brass is a combination of copper (cu) and zinc (zn), one of the way the brass works with casting, the evaporative casting method is casting polystyrene foam as a immersed pattern of the sand cast, the casting method has a superior degree of precision. In order to increase the power of the brass yield, the study is conducted on a variation in the size of the sand on the power impact and morphology of the brass yield on the evaporative foundry.The study conducted a brass casting process with evaporative casting methods by casting temperature with a release of 900 concentrated casting done by varying the size of silica 0.250; 0.315; 0.500 mm. The test impact obtained the highest impact value on a specimen measuring 0.250mm of sand grains that had an average of 0.26nm /mm mm mm. Whereas the value of the lowest impact force was obtained on a specimen of 0.500mm sand grains that had an average of 0.24nm /mm mm difference. Observations of macrostructure in a specimen that measures 0.250mm of sand tend to have tight density. Whereas the size of the 0.500 grains of sand tends to have a slight density, causing a very low value impact force to be mitigated by the size of the 0.250 grains of sand. So the longer freezing of molten metal the more intense it gets.. Keywords: Evaporative Casting, Polystyrene Foam, Impack Testing, Macro Structure